Non-coding RNA networks regulating leaf vegetative desiccation tolerance in the resurrection plant Xerophyta humilis. - Milborrow, Evan (Department of Molecular and Cell Biology, 2019)
Common to orthodox seeds, desiccation tolerance (DT) is exceedingly rare in the vegetative tissues of modern angiosperms, being limited to a small number of "resurrection plants". While the molecular mechanisms of DT, as well as the transcription factors regulating the seed and vegetative DT programmes, have been identified, very little is known with regards to the role of regulatory noncoding RNAs (ncRNAs). To investigate the presence and roles of possible ncRNA players, RNA-Seq was performed on desiccating Xerophyta humilis leaves and a bioinformatic pipeline assembled to identify the potential decoy lncRNAs and miRNAs present. Interaction mapping was performed, identifying a number of small regulatory networks each regulating a small subset of the desiccation transcriptome. Predicted networks were screened for function related to DT and expression consistent with functional regulatory interactions. Of the predicted networks, two appear highly promising as potential regulators of key DT response genes. The results indicate that differentially expressed (DE) desiccation response ncRNAs are present in the vegetative tissues of X. humilis and likely play a key role in the regulation of DT. This suggests that ncRNAs appear to play a more important role in DT than previously thought, and may have facilitated the evolution of vegetative DT through reprogramming of seed DT programs in vegetative tissues.